Long-term efficacy and safety of vestronidase alfa enzyme replacement therapy in pediatric subjects < 5 years with mucopolysaccharidosis VII - Lau, Heather A.; Viskochil, David; Tanpaiboon, Pranoot; Lopez, Antonio Gonzalez-Meneses; Martins, Esmeralda; Taylor, Julie; Malkus, Betsy; Zhang, Lin; Jurecka, Agnieszka; Marsden, Deborah (Molecular genetics and metabolism, 2022)
Mucopolysaccharidosis (MPS) VII is an ultra-rare, autosomal-recessive, metabolic disease caused by a deficiency of β-glucuronidase, a lysosomal enzyme that hydrolyzes glycosaminoglycans (GAGs), including dermatan sulfate (DS), chondroitin sulfate, and heparan sulfate (HS). β-glucuronidase deficiency leads to progressive accumulation of undegraded GAGs in lysosomes of affected tissues, which may cause hydrops fetalis, short stature, hepatosplenomegaly, and cognitive impairment. An open-label, multicenter, phase II study was conducted in 8 pediatric subjects <5 years of age with MPS VII. Subjects received the recombinant human β-glucuronidase vestronidase alfa 4 mg/kg by intravenous infusion every other week for 48 weeks (treatment period). Those who completed the 48-week treatment were offered to continue treatment with vestronidase alfa 4 mg/kg for up to 240 weeks or until withdrawal of consent, discontinuation, or study termination (continuation period). The level of GAG excreted in urine (uGAG) above normal has been shown to correlate with disease severity and clinical outcomes in MPS diseases. Therefore, the primary efficacy endpoint of this study was to determine the mean percentage change in uGAG DS excretion from baseline to week 48. Statistically significant reductions in uGAG DS from baseline were observed at each visit (p < 0.0001), with a least square mean (standard error) percentage change of −60% (6.6) at week 4 (first post-baseline assessment) and −61% (6.41) at week 48 (final assessment during treatment period). Secondary efficacy endpoints included change from baseline to week 48 in growth and hepatosplenomegaly. Positive trends were observed toward increased standing height Z-score (mean [standard deviation] at baseline, −2.630 [1.17], n = 8; at week 48, −2.045 [0.27], n = 7) and growth velocity (mean [SD] Z-score at baseline, −2.59 [1.49], n = 4; at week 48, −0.39 [2.10], n = 4; p = 0.27). Hepatomegaly was resolved in 3 of 3 subjects assessed by ultrasound and in 5 of 6 subjects assessed by physical examination; splenomegaly was resolved in 1 of 3 subjects assessed by ultrasound and in 2 of 2 subjects assessed by physical examination. There were no new safety signals identified during this study. Mild-to-moderate infusion-associated reactions occurred in 4 (50%) subjects. In conclusion, long-term vestronidase alfa treatment demonstrated a rapid and sustained reduction in uGAGs, maintained growth, and improved hepatosplenomegaly in pediatric subjects with MPS VII <5 years of age. Trial registration: NCT02418455.